Evolution of Transdermal Drug Delivery Devices and Novel Microneedle Technologies: A Historical Perspective and Review - Naveen Joshi; Sina Azizi Machekposhti; Roger J. Narayan (Elsevier, 2023)
The history of transdermal drug delivery is as old as humankind. Transdermal drug delivery has undergone three generations of development; the third generation has involved the use of medical devices and instruments. This review provides a historical perspective on the primary approaches employed in the three generations of transdermal drug delivery. In addition, we explore some of the recently developed transdermal techniques that are deemed promising in the field of drug delivery. We discuss how advances in these techniques have led to the development of devices for the delivery of a therapeutically effective amount of drug across human skin and highlight the limitations of the first- and second-generation drug delivery tools. As such, a review of the performance of these techniques and the toxicity of the devices used in transdermal drug delivery are considered. In the last section of the review, a discussion of the fabrication and operation of different types of microneedles is presented. The applications of microneedles in the sensing and delivery of various therapeutic agents are described in detail. Furthermore, an overview of the efficacy of microneedles as emerging tools for the controlled release of drugs is presented.